A study of job satisfaction and tax complexity. (16th April 2009) - Stathopoulos, Xenia; Wise, Victoria
The introduction of the Income Tax Assessment Act 1997 (Australia) was an attempt to decrease the complexity of the tax system, but the issue of complexity is still evident. Accounting practitioners are becoming overwhelmed with the amount of tax legislation and researchers have suggested that they are less satisfied in their jobs as a result. This study examines whether tax complexity affects accounting practitioners' job satisfaction. Demographic and personality factors are considered. The issues that were investigated further include practitioner perceptions of the most complex area(s) of tax law and the primary causes of a complex tax system. It was found that although tax complexity is causing job dissatisfaction, demographic factors and personality characteristics do not appear to be significant factors. Instead, the large volume of tax law was identified as having the most significant impact on complexity (resulting in widespread dissatisfaction) and income tax was regarded as the most complex area.